Edukasi GERKASA-LASAKIT (Gerakan Lansia Sehat Sadar Penyakit) - Nur Indah Nasution; Nadya Fitriani (STIKES Columbia Asia Medan, 2025)
This community service project aims to raise awareness and knowledge about health among the elderly through the GERKASA-LASAKIT program (Movement for Healthy and Disease-Aware Seniors) in Dusun 1, Tanjung Anom Village, Deli Serdang Regency. This initiative is driven by the high prevalence of degenerative diseases and the lack of accurate information regarding the prevention and management of these diseases among seniors. Through comprehensive health education, it is hoped that the elderly can improve their quality of life by adopting a healthy lifestyle and gaining a better understanding of common illnesses they may face. The methods used in this project include health education sessions, practical training on early disease detection, and physical activities tailored to the physical condition of the elderly. Health education is provided by medical professionals and public health experts. Additionally, individual consultation sessions are held to offer more personalized care for each participant. The results of this activity show an increase in health knowledge and awareness among the elderly, as evidenced by high participation and enthusiasm in each session. Seniors involved in this program have also begun adopting healthier lifestyles, such as engaging in regular light exercise and having routine health check-ups. This project has successfully built a support network among the elderly, their families, and the local community, creating a more caring and health-conscious environment. Thus, the GERKASA-LASAKIT program makes a significant contribution to improving the quality of life for the elderly in Dusun 1, Tanjung Anom Village. The sustainability of this program is expected to serve as a model for other villages in efforts to enhance the welfare and health of the elderly at the local level.